Free fatty acid content in subcutaneous and visceral fat tisssue in postmenopausal overweight and obese women. The influence on lipid profile. Data from central Poland population - Połać, Ireneusz; Pytasz, Urszula; Stachowiak, Grzegorz; Stetkiewicz, Tomasz; Pakalski, Andrzej; Jędrzejczyk, Sławomir; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2005)
Fatty acids composition was evaluated in subcutaneous and visceral fat tissue in population of postmenopausal women in central Poland. Fatty acids composition in tissues and normal diet was compared. Effect of selected fatty acids concentrations on serum lipid profile was examined. We noted that polyunsaturated acids content in tissues correlate with these acids content in diet, but there is no such correlation in case of saturated and monounsaturated acids. We observed correlations between selected acids concentrations in tissues and serum lipids.